Validation of the SunTech Medical Advantage Model 2 Series Automated Blood Pressure Module in Pregnancy - Kuper, Spencer G.; Dotson, Kristin N.; Anderson, Sarah B.; Harris, Stacy L.; Harper, Lorie M.; Tita, Alan T. (American Journal of Perinatology, 2019)
Objective We sought to validate the SunTech Medical Advantage Model 2 Series with firmware LX 3.40.8 algorithm noninvasive blood pressure module in a pregnant population, including those with preeclampsia.Study Design Validation study of an oscillometric noninvasive blood pressure module using the ANSI/AAMI ISO 81060-2:2013 standard guidelines. Pregnant women were enrolled into three subgroups: normotensive, hypertensive without proteinuria, and preeclampsia (hypertensive with random protein-to-creatinine ratio ≥ 0.3 or a 24-hour urine protein > 300 mg). Two trained research nurses, blinded to each other's measurements, used a mercury sphygmomanometer to validate the module by following the protocol set forth in the ANSI/AAMI ISO 81060-2:2013 standard guidelines.Results A total of 45 patients, 15 in each subgroup, were included. The mean systolic and diastolic differences with standard deviations between the module and the mean observers' measurements for all participants were −2.3 ± 7.3 and 0.2 ± 6.5 mm Hg, respectively. The systolic and diastolic standard deviations of the mean of the individual patient's paired module and observers' measurements were 6.27 and 5.98 mm Hg, respectively. The test device, relative to a mercury sphygmomanometer, underestimated the systolic blood pressure in patients with preeclampsia by at least 10 mm Hg in 24% (11/45) of paired measurements.Conclusion The SunTech Medical Advantage Model 2 Series with firmware LX 3.40.8 algorithm noninvasive blood pressure module is validated in pregnancy, including patients with preeclampsia; however, it may underestimate systolic blood pressure measurements in patients with preeclampsia.
Keywords: ANSI/AAMI ISO 81060-2:2013; automated blood pressure device; blood pressure module; preeclampsia; pregnancy; validation